Renal replacement therapy as a possible trauma in acute kidney injury - John, Stefan (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2014)
Renal replacement therapy (RRT) is not able to replace all of the physiologic functions of the kidney. Moreover renal replacement therapy can be associated with a number of serious side effects and complications which can alter the natural course and prognosis of critically ill patients.Contributing to this RRT trauma are hemodynamic changes induced by RRT, the induction of inflammation by the extracorporeal circuit itself, side effects of anticoagulation, but especially often unwanted and not recognized losses of multiple substances by the blood purification itself.Therefore, the aim should be to adapt therapy in a way that systemic and renal side effects can be minimized or replaced. These include the correct selection of the RRT modality for each patient and each individual clinical situation, in prescribing and monitoring an individual dose of RRT, and the substitution of unwanted losses of different substances. Especially in septic patients, antimicrobials have to be prescribed carefully during the first 72 h, during which underdosing of these substances is a real danger in patients on renal replacement therapy.
EVALuna2:3693